2016
DOI: 10.1002/jocb.145
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of a theoretical model for mathematical creativity

Abstract: In this exploratory study, a theoretical model proposed by Sriraman (2005) consisting of five theoretical principles for optimizing creativity in a K-12 setting was investigated empirically. This was accomplished in two steps. In the first study, the five principles were operationalized by generating a questionnaire consisting of 45 items intended to capture the dimension of each principle. An exploratory maximum-likelihood factor analysis indicated a relatively robust five factor structure that corresponded w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 47 publications
0
16
0
3
Order By: Relevance
“…In line with the reviewed literature focusing mostly on children and adolescents, we expected to find a positive relationship between intelligence and mathematical creativity (e.g., Kroesbergen and Schoevers 2017 ; Kahveci and Akgul 2019 ; Kattou and Christou 2017 ), and differentiated relationships between the sub-facets of verbal, numerical, and figural intelligence and mathematical creativity. Further, we expected a positive relationship between mathematical competence and mathematical creativity (e.g., Chen et al 2006 ; Bahar and Maker 2011 ; Haavold 2016 ; Karwowski et al 2020 ; Schoevers et al 2018 ). Additionally, based on the discussed results (e.g., Lin and Cho 2011 ; Schoevers et al 2018 ), we expected general creativity to have a positive relationship with mathematical creativity in adults.…”
Section: Introductionmentioning
confidence: 97%
“…In line with the reviewed literature focusing mostly on children and adolescents, we expected to find a positive relationship between intelligence and mathematical creativity (e.g., Kroesbergen and Schoevers 2017 ; Kahveci and Akgul 2019 ; Kattou and Christou 2017 ), and differentiated relationships between the sub-facets of verbal, numerical, and figural intelligence and mathematical creativity. Further, we expected a positive relationship between mathematical competence and mathematical creativity (e.g., Chen et al 2006 ; Bahar and Maker 2011 ; Haavold 2016 ; Karwowski et al 2020 ; Schoevers et al 2018 ). Additionally, based on the discussed results (e.g., Lin and Cho 2011 ; Schoevers et al 2018 ), we expected general creativity to have a positive relationship with mathematical creativity in adults.…”
Section: Introductionmentioning
confidence: 97%
“…Proposta de atividade lúdica como auxílio ao ensino de zoologiarevisão e fixação em sala de aula. (GONTIJO, 2007;FONSECA, 2015;HAVOOLD, 2016;PETROVICI;HAV RNEANU, 2015;KATTOU et. al., 2013).…”
Section: Discussionunclassified
“…These findings are in line with previous research. Several studies have reported that there is a positive and significant relationship between mathematical knowledge and mathematical creativity (see for instance Haavold, ; Mann, and Kadir & Maker, ). Other studies (see for instance Bahar & Maker, ; Sak & Maker, ; Tabach & Friedlander, ) have also found a significant effect of age and grade level on mathematical creativity.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the nature of the tasks in the test favored the younger students, for instance as concepts could have been recently addressed in coursework. However, the test has previously been piloted, and found to be appropriate for older students (Haavold, ).…”
Section: Limitationsmentioning
confidence: 99%